Coherent Optical Interleaved SC-FDM Uplink Scheme for Long-Reach Passive Optical Network - Ji Zhou; Fei Xu; Erkun Sun; Tiantian Zhang; Zhenshan Zhang; Mengqi Guo; Xizi Tang; Zhansheng Wang; Yaojun Qiao (IEEE Photonics Journal, 2016)
In this paper, we propose a coherent optical interleaved single-carrier frequency-division multiplexing (CO-I-SC-FDM) uplink scheme for the long-reach passive optical network (LR-PON). I-SC-FDM is a modified form of orthogonal frequency-division multiplexing (OFDM) with low computational complexity and low peak-to-average power ratio (PAPR). By designing a simple encoding structure, the computational complexity of the transmitter can be reduced from $O(Nlog_{2}(N))$ to $O(N)$ . At the probability of $10^{-3}$ , the PAPR of the I-SC-FDM is about 10.7 dB lower than that of conventional OFDM for quadrature phase-shift keying (QPSK) modulation. We experimentally demonstrate a 10-Gb/s CO-I-SC-FDM uplink scheme over 100-km standard single-mode fiber with 1:128-way passive splitter for LR-PON. In the conventional CO-OFDM uplink scheme, the splitting ratio is only 1:64. The proposed scheme shows great potential for application in access and metro networks.